The Symbolization of the Kukuak Balenggek Chicken Statue, Solok Regency, West Sumatra Province: Analysis of Cultural Mythology - Rahmi Masfi; Mafardi (GoAcademica Research & Publishing, 2022)
This study discusses the meaning of community knowledge in Solok Regency, West Sumatra towards the Ayam Kukuak Balenggek statue. The Kukuak Balenggek Chicken Statue is located in Solok Regency which was appointed as an icon of Solok Regency which was founded by the local government authority of Solok Regency. The data collection method is carried out with in-depth interviews, observations, documentation, and literature studies. The results of this study show the understanding from the public about the figure of Ayam Kukuak Balenggek which can be seen from the nature and philosophy of Ayam Kukuak Balenggek in depth and authentically.